P210 Are sputum and blood biomarkers of inflammation repeatable in stable COPD?. (19th November 2012) - Barker, BL; Mistry, V; Pancholi, M; Brightling, CE; Bafadhel, M
Abstract : Background: Spirometry is a commonly used end-point in COPD clinical trials and there is evidence that spirometric values are reproducible in COPD patients. COPD is heterogeneous and differences in biomarkers of pulmonary and systemic inflammation between patients can be identified. Currently limited short-term reproducibility is available in stable COPD. Aims: Assess repeatability of commonly used clinical measures in subjects with stable COPD over 3 and 6 months. Methods: Subjects with COPD were enrolled into an observational study and were reviewed at stable visits after 3 and 6 months. Spirometry, blood [peripheral blood total white cell and differential cell counts] and sputum [sputum differential cell counts (%)] markers of inflammation were repeated at each visit. Repeatability of these measures was assessed using the intra-class correlation coefficient (Ri) and is expressed below as Ri (95%CI). Results: 145 subjects were recruited; 101 were male with a mean (SD) FEV1 (L) and FEV1/FVC ratio (%) of 1.34 L (0.57) and 53% (14.6) respectively. Spirometry values showed excellent repeatability; FEV1 [0.93 (0.84 to 0.92) and 0.89 (0.83 to 0.92)] and FVC [0.80 (0.73 to 0.86) and 0.81 (0.72 to 0.87)] after 3 and 6 months respectively. Sputum biomarkers of inflammation showed moderate repeatability at 3 and 6 months respectively; sputum neutrophils (%) [0.59 (0.43 to 0.71) and 0.50 (0.33 to 0.64)] and eosinophils (%) [0.62 (0.48 to 0.73) and 0.32 (0.13 to 0.49)]. The blood biomarkers peripheral blood white cell count (WCC), neutrophil and eosinophil counts demonstrated good repeatability after 3 and 6 month intervals respectively; WCC [0.68 (0.56 to 0.77) and 0.73 (0.62 to 0.81)], neutrophil count [0.66 (0.54 to 0.76) and 0.71 (0.59 to 0.79)] and eosinophil count [0.66 (0.54 to 0.76) and 0.73 (0.63 t o0.81)]. CRP showed fair repeatability [0.34 (0.16 to 0.5) and 0.30 (0.11 to 0.47) at both time intervals. Discussions: Sputum differential cell counts (%) and peripheral blood differential cell counts are repeatable after 3 and 6 month intervals. These findings may have clinical implications when targeting therapies to sub-groups of COPD patients.